note:
log (xy) = log x + log y
and
log (x/y) = log x - log y
therefore:
log (36/5) + log (3/2) - log (6/5)
= log {[(36/5)(3/2)]/(6/5)}
= log {(36/5)(3/2)(5/6)}
= log {(3)(2)(6/5)(3)(1/2)(5/6)
= log 9
= log (3^2)
since your base is 3
and
log (a^n) to the base a = n
therefore
log (36/5) + log (3/2) - log (6/5) = 2
2007-03-06 22:15:02
·
answer #1
·
answered by datz 2
·
0⤊
0⤋
Assume all logs are to base 3 in the following:-
log [(36/5 x 3/2) / 6/5 ]
= log [(54/5) / (6/5)]
= log (9) = 2
2007-03-06 22:28:29
·
answer #2
·
answered by Como 7
·
0⤊
0⤋
Using logx + logy = log(xy) and
logx - logy = log(x/y)
we get
log((36/5)*(3/2)/(6/5))
= log((36/5)*(3/2)*(5/6))
= log(9)
Since the log base is 3, and 90 = 3^2,
the answer is 2.
2007-03-06 22:00:37
·
answer #3
·
answered by Hy 7
·
0⤊
0⤋
write as log[(36/5 * 3/2)/(6/5)]
You can simplify the rest
2007-03-06 21:58:45
·
answer #4
·
answered by leo 6
·
0⤊
0⤋
log3/5 over log3/36+log3/2-log3/5 over log3/6
=(log3/5 over log3/36)*log3/2*( log3/6 over log3/5)
=(5 over 36)*2*ï¼6 over 5)
=1 over 3
* refer to times
2007-03-07 00:39:18
·
answer #5
·
answered by Ivy 1
·
0⤊
0⤋
answer is 2
simplification is available at
http://www.geocities.com/regform20052007/mathpro21/1.html
2007-03-07 03:49:53
·
answer #6
·
answered by qwert 5
·
0⤊
0⤋